A Bright Future for Evolutionary Methods in Drug Design. Issue 8 (9th June 2015) - Le, Tu C.; Winkler, David A.
Abstract Most medicinal chemists understand that chemical space is extremely large, essentially infinite. Although high‐throughput experimental methods allow exploration of drug‐like space more rapidly, they are still insufficient to fully exploit the opportunities that such large chemical space offers. Evolutionary methods can synergistically blend automated synthesis and characterization methods with computational design to identify promising regions of chemical space more efficiently. We describe how evolutionary methods are implemented, and provide examples of published drug development research in which these methods have generated molecules with increased efficacy. We anticipate that evolutionary methods will play an important role in future drug discovery.